A comprehensive literature review of Forensic Assertive Community Treatment (FACT): Directions for practice, policy and research. Issue 2 (2nd April 2020) - Cuddeback, Gary S.; Simpson, Jennie M.; Wu, Juliet C.
Abstract: Forensic assertive community treatment (FACT) is an adaptation of Assertive Community Treatment (ACT), a widely-studied evidence-based model for mental health services delivery. ACT has been demonstrated to reduce psychiatric hospitalizations and improve community tenure, however, research on the adaptations needed to target criminogenic risks and needs and reduce recidivism for individuals living with serious mental illnesses who are justice involved is in its nascent stages. This literature review was undertaken to establish the current state of research on the FACT model. An analysis was conducted of 47 peer-reviewed research articles and book chapters to identify themes in FACT eligibility criteria, staffing and competencies, models, sustainability, and outcomes of FACT. The paper provides an overview of the research to-date on FACT and offers recommendations for practice, policy, and research. At this stage, research is needed to better understand for whom does FACT work, under what circumstances, and with what outcomes.